Large dam development and displacement : understanding reasons and dynamics for conflict over construction of Polihali dam in Mokhotlong District - Thebe, Vusilizwe (University of Pretoria, 2021)
Dissertation(MSocSci (Development Studies))--University of Pretoria 2020.